The effect of brand trust and brand community commitment on online brand evangelism behaviour - Shaari, Hasnizam; Ahmad, Intan Shafinaz (Universiti Utara Malaysia, 2016)
In line with social media development, the online brand community becomes an alternative media that could contribute to overall brand success or vice versa.Among others, the online brand community could significantly affect brand evangelism behaviors.This study attempts to extend the understanding on how members’ brand community commitment influences brand evangelism which is considered as an extra-role behavior from the members.The study among 167 members of the online brand communities revealed that brand evangelism is explained by the uni dimensional construct.The result indicates that trust towards the online brand community and brand community commitment significantly affect brand evangelism.Implication and future research direction are also highlighted at the end of this article.